2018
DOI: 10.3389/fnhum.2018.00211
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Brain Stimulation: A Paradigm Shift in Understanding Brain Oscillations

Abstract: Cognitive neuroscience set out to understand the neural mechanisms underlying cognition. One central question is how oscillatory brain activity relates to cognitive processes. Up to now, most of the evidence supporting this relationship was correlative in nature. This situation changed dramatically with the recent development of non-invasive brain stimulation (NIBS) techniques, which open up new vistas for neuroscience by allowing researchers for the first time to validate their correlational theories by manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(196 citation statements)
references
References 153 publications
4
166
1
1
Order By: Relevance
“…This finding is difficult to reconcile with a stimulation effect mediated by entrainment. While in animal studies online effects were found to be directly related to an entrainment of ongoing neural activity by the applied electric oscillation (Ozen et al, 2010;Reato et al, 2010;Fröhlich & McCormick, 2010), in human studies investigating post-stimulation modulations of oscillations it was proposed that these offline effects may stem from LTP/LTD related effects (Vossen et al, 2015;Zaehle et al, 2010;Vosskuhl et al, 2018). Like others, we previously reported on tACS driven decreases in the amplitude of ongoing oscillations (Garside et al, 2015;Gundlach et al, 2017).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This finding is difficult to reconcile with a stimulation effect mediated by entrainment. While in animal studies online effects were found to be directly related to an entrainment of ongoing neural activity by the applied electric oscillation (Ozen et al, 2010;Reato et al, 2010;Fröhlich & McCormick, 2010), in human studies investigating post-stimulation modulations of oscillations it was proposed that these offline effects may stem from LTP/LTD related effects (Vossen et al, 2015;Zaehle et al, 2010;Vosskuhl et al, 2018). Like others, we previously reported on tACS driven decreases in the amplitude of ongoing oscillations (Garside et al, 2015;Gundlach et al, 2017).…”
Section: Discussionsupporting
confidence: 51%
“…Non-invasive brain stimulation (NIBS) technology has gained increasing attention in the last few years from the scientific community (Bergmann et al, 2016;Thut et al, 2017;Antal et al, 2017;Vosskuhl et al, 2018), clinical (Yavari et al, 2017;Palm et al, 2014), sports (Edwards et al, 2017;Angius et al, 2018), military (Nelson et al, 2016), and other fields. One of the reasons for this growing interest is the successful modulation of cognitive, motor, and perceptual functions in numerous studies in different domains such as motor function (Brittain et al, 2013;Angius et al, 2018), visual (Helfrich et al, 2014;Zaehle et al, 2010), auditory (Riecke et al, 2015), somatosensory Gundlach et al, 2016Gundlach et al, , 2017, or linguistic processing (Riecke et al, 2018;Wilsch et al, 2018) and for higher cognitive functions such as decision making, creativity, or self-aware dreaming (Lustenberger et al, 2015;Sela et al, 2012;Voss et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the current that actually reaches neural tissue is relatively weak Opitz et al, 2016). This issue has led to ongoing debates about whether and how tACS can manipulate neural activity (Krause, Vieira, Csorba, Pilly, & Pack, 2019;Lafon et al, 2017;Opitz, Falchier, Linn, Milham, & Schroeder, 2017;Ruhnau, Rufener, Heinze, & Zaehle, 2018;Vöröslakos et al, 2018;Vosskuhl, Strüber, & Herrmann, 2018). Our study addresses two experimental variableselectrode montage and statistical analysiswhich need to be carefully considered in tACS studies of speech processing.…”
Section: Methodsological Implicationsmentioning
confidence: 99%
“…In a peak frequency informed analysis, a selection was made based on the proximity of the stimulation frequency to the frequency of endogenous oscillations in the stimulated brain area, since this proximity can influence the degree of neural entrainment induced by tACS [49]. As power spectra displayed clear peaks of endogenous oscillations at alpha frequencies over S1 exclusively, this analysis was only applied to the S1 alpha condition.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…Transcranial alternating current stimulation (tACS) is an emerging neuromodulation technique which aims at non-invasively modulating neural oscillations in the human brain. During tACS, a weak alternating current is applied to the scalp with the goal of entraining neural oscillations at the stimulation frequency [33,49]. The appeal of the tACS is that it is non-invasive, safe, cost-efficient, and potentially mobile which allows for broad applications in clinical settings [15].…”
Section: Introductionmentioning
confidence: 99%